IMF Staff papers, Volume 43 No. 3. (IMF Staff Papers; IMF Staff Papers ;, 1996)
This paper examines the volatility and predictability of emerging stock markets. A range of measures suggests that, despite perceptions to the contrary, the volatility of emerging markets may have fallen rather than risen on average. Also, although the autocorrelations in emerging market returns appear to turn negative at horizons of a year or more, the magnitude of these return reversals is not that much larger than reversals in some mature markets. One interpretation of the results would be that emerging markets have not consistently been subject to fads or bubbles, or at least no more so than in some industrial countries.